Alternatives For Resolving Consumer Disputes Through Consumer Settlement Agency Reviewed From The Consumer Protection Law - Arya Syahputra Wijaya; Christine S. T. Kansil (CV Rewang Rencang, 2024)
The consumer dispute resolution is a significant issue in consumer protection practices in Indonesia. One of the settlement mechanisms regulated in the Consumer Protection Law is through the Consumer Dispute Settlement Agency. This article aims to analyze the advantages and disadvantages of dispute resolution through the Consumer Dispute Settlement Agency and evaluate its effectiveness as an alternative to consumer dispute resolution. This study uses a normative juridical approach by analyzing related laws and regulations as well as case studies in the implementation of the Consumer Dispute Settlement Agency. The results of the study show that the advantages of Consumer Dispute Settlement Agency include a fast process, low cost, and consumer favoritism. However, the main weaknesses lie in the limitations of the Consumer Dispute Settlement Agency’s authority, the quality of human resources, and the implementation of decisions that are not optimal. In terms of effectiveness, Consumer Dispute Settlement Agency is able to be an alternative solution that is quite adequate for consumers with minor disputes, but still needs to improve regulations and strengthen capacity to be more effective. This study concludes that Consumer Dispute Settlement Agency has great potential in supporting consumer protection, as long as the existing obstacles can be overcome through better policy reform and supervision.